Systemic Approach to Teaching the Meaning, Use, Spelling and Pronunciation of English Adjectives: A Quasi-Experimental Study - Alwiah, Wiwik; Israil, Irnawati (Global Education Journal, 2025)
This study aimed to investigate the effectiveness of using the systemic approach to improve students’ understanding of English adjectives, specifically in relation to spelling, pronunciation meaning, and use. This research employed a quasi-experimental design. The population consisted of third-semester students of Muhammadiyah University of Makassar in the 2017/2018 academic year. A total of 40 students were selected through purposive sampling and were divided into two groups namely an experimental group and a control group. The experimental group was taught using the systemic approach, which emphasized the intersection, interaction, and interrelation of linguistic elements, while the control group received instruction using conventional methods. The findings showed that the systemic approach led to significantly better outcomes. Post-test t-test results revealed scores of 6.363 for use, 7.131 for spelling, 6.309 for meaning, and 6.397 for pronunciation, all exceeding the critical t-table value of 2.024. These results indicated statistically significant improvements across all assessed aspects. This study concluded that the systemic approach supported integrative and effective learning of adjectives by helping students master not only their form but also their practical application.